Experimental investigation of cementitious material-filled square thin-walled steel beams. (May 2017) - Hassanein, M.F.; Kharoob, O.F.; Taman, M.H.
Abstract: It was recently found that concrete-filled steel tubular (CFST) beams have some advantages in resisting forces compared to steel tubular beams. By using the CFST beams, the flexural capacity, stiffness, ductility and energy dissipation ability are improved due to the presence of the filled-in concrete. Currently, bending tests are performed on glass-fibre reinforced cementitious material-filled square steel tubular (GFCMFST) beams. For comparison, unreinforced cementitious material-filled square steel tubular (CMFST) beams with a higher compressive strength are also prepared and tested. Two shear span-to-depth ratios are considered in the tests. The tests showed that all beams have a significant yielding plateau, hence, exhibit adequate ductility. Furthermore, it was found that the first crack of the filling material took place for CMFST beams at lower load levels compared to the GFCMFST beams in spite having higher compressive strength. Also, it was found that the stresses of the CMFST beams were always greater than the corresponding values of GFCMFST beams in both the tensioned and the compressed zones. The experimental moment capacities were then compared with the available design methods. It is recommended to use the design strength as estimated following EC4. Comparisons between the experimental results of the initial and the serviceability-level section flexural stiffness and its corresponding values from literature and design specifications were also made. Among the different methods, the AIJ standard was found to give the most suitable results for the initial section flexural stiffness and the serviceability-level section flexural stiffness of the current composite beams. Highlights: Behaviour of cementitious material-filled steel tubes under bending is presented. Both glass-fibre reinforced and unreinforced cementitious materials are used. The design strength given by the EC4 is recommended. The section flexural stiffnesses are compared by the design specifications.